2022
DOI: 10.3389/fphar.2021.805222
|View full text |Cite
|
Sign up to set email alerts
|

Paeonol Ameliorates Chronic Itch and Spinal Astrocytic Activation via CXCR3 in an Experimental Dry Skin Model in Mice

Abstract: Paeonol is a bioactive phenol presents mainly in Paeonia suffruticosa Andr. (Paeoniaceae), Paeonia lactiflora Pall., and Dioscorea japonica Thunb. (Dioscoreaceae), harboring various pharmacological activities including anti-inflammatory, antioxidant, immune regulatory activity and reverse chemoresistance. Recent reports revealed paeonol exhibited good effects on chronic dermatitis, such as atopic dermatitis (AD) and psoriasis. However, whether paeonol is effective for dry skin disease and its mechanism of acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…Afterward, a total of 72 female mice were randomly divided into six groups: control group ( n = 12), PE group ( n = 12), PE mice administered a low dose (50 mg/kg/d) of Pae (PE + Pae 10 group [ n = 12]) from GD0 to GD17, PE mice administered a medium dose (100 mg/kg/d) of Pae (PE + Pae 100 group [ n = 12]) from GD0 to GD17, PE mice administered a high dose (150 mg/kg/d) of Pae (PE + Pae 150 group [ n = 12]) from GD0 to GD17, and Pae‐treated PE mice intraperitoneally injected with 8 mg/kg of SC‐39100 on GD17 (SC‐39100 + PE + Pae 150 [ n = 12]). The dosages of Pae and SC‐39100 were selected in accordance with previous documents 18–20 . On GD18, all mice were sacrificed, and the placental tissues were collected and stored in liquid nitrogen at −80°C for later use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Afterward, a total of 72 female mice were randomly divided into six groups: control group ( n = 12), PE group ( n = 12), PE mice administered a low dose (50 mg/kg/d) of Pae (PE + Pae 10 group [ n = 12]) from GD0 to GD17, PE mice administered a medium dose (100 mg/kg/d) of Pae (PE + Pae 100 group [ n = 12]) from GD0 to GD17, PE mice administered a high dose (150 mg/kg/d) of Pae (PE + Pae 150 group [ n = 12]) from GD0 to GD17, and Pae‐treated PE mice intraperitoneally injected with 8 mg/kg of SC‐39100 on GD17 (SC‐39100 + PE + Pae 150 [ n = 12]). The dosages of Pae and SC‐39100 were selected in accordance with previous documents 18–20 . On GD18, all mice were sacrificed, and the placental tissues were collected and stored in liquid nitrogen at −80°C for later use.…”
Section: Methodsmentioning
confidence: 99%
“…The dosages of Pae and SC-39100 were selected in accordance with previous documents. [18][19][20] On GD18, all mice were sacrificed, and the placental tissues were collected and stored in liquid nitrogen at À80 C for later use.…”
Section: Introductionmentioning
confidence: 99%
“…P. × suffruticosa bark root extracts also have scientifically proven cosmetic properties, such as: antioxidant, anti-aging and skin brightening [ 86 , 87 ]. Recent reports revealed paeonol from P. × suffruticosa exhibited good effects on chronic dermatitis, such as atopic dermatitis (AD) and psoriasis [ 88 ].…”
Section: Paeonia × Suffruticosa As a New Pharmacopoeial Plan...mentioning
confidence: 99%
“…The results showed impressive activities in reducing scratching behavior and skin inflammation. The studies indicated that paeonol can ameliorate AEW-induced inflammatory response and itching behavior and reduce the expression of spinal astrocyte activity-dependent genes induced by AEW, reducing the expression of spinal astrocyte activity-dependent genes induced by AEW [ 88 ].…”
Section: Applications In Cosmetologymentioning
confidence: 99%
“…In diabetes rats, PAE‐treatment repressed the expression of NF‐κB and MCP‐1 and alleviated diabetes‐induced sciatic nerve damage (Adki & Kulkarni, 2021). Additionally, PAE efficiently restrained CXCR3 pathway‐activated astrocytes in mouse model of dry skin (Wang et al, 2021). However, whether PAE could suppress astrocytes activation and the potential underlying mechanisms in NP are still unknown.…”
Section: Introductionmentioning
confidence: 99%